Blockade of Asparagine Endopeptidase Inhibits Cancer Metastasis - Qi, Qi (J Med Chem, 2017)
Asparagine endopeptidase (AEP), also called legumain, is highly expressed in various solid tumors, promoting cancer cell invasion, migration, and metastasis. It has been proposed to be a prognostic marker and therapeutic target for cancer treatment. However, an effective nonpeptide, smallmolecule inhibitor against this protease has not yet been identified. Here we show that a family of xanthine derivatives selectively inhibit AEP and suppress matrix metalloproteinase (MMP) cleavage, leading to the inhibition of cancer metastasis. Through structure–activity relationship (SAR) analysis, we obtained an optimized lead compound (38u) that represses breast cancer invasion and migration. Chronic treatment of nude mice, which had been inoculated with MDA-MB-231 cells, with inhibitor 38u via oral administration robustly inhibits breast cancer lung metastasis in a dose-dependent manner, associated with blockade of MMP-2 by AEP. Therefore, our study supports that 38u might act as a potent and specific AEP inhibitor useful for cancer treatment.